The changing nature of the school-to-work transition process in OECD countries - Glenda Quintini; John P. Martin; Sébastien Martin (Institute for the Study of Labor (IZA), 2007)
Despite the fact that today's young cohorts are smaller in number and better educated than their older counterparts, high youth unemployment remains a serious problem in many OECD countries. This reflects a variety of factors, including the relatively high proportion of young people leaving school without a basic education qualification, the fact that skills acquired in initial education are not always well adapted to labour market requirements, as well as general labour market conditions and problems in the functioning of labour markets. The paper highlights the contrasting trends in youth labour market performance over the past decade using a wide range of indicators. It also presents new evidence on i) the length of transitions from school to work; and ii) the degree to which temporary jobs serve as either traps for young people or stepping-stones to good careers. In addition, the paper reviews some recent policy innovations to improve youth employment prospects
urn:nbn:de:101:1-20080425121
Keywords: 330; Jugendarbeitslosigkeit; Berufseinstieg; Arbeitsverhältnis; Arbeitsmarktpolitik; OECD-Staaten